2001
DOI: 10.1667/0033-7587(2001)156[0607:mimcib]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Mammalian Cells Induced by Heavy Charged Particles: An Indicator for Risk Assessment in Space

Abstract: Induction of mutations at the HPRT locus in V79 Chinese hamster cells by heavy charged particles is reviewed. A unique dependence of mutation induction cross sections on LET or any other physical parameter of the particles cannot be found. There is, however, a general trend showing an increase up to about 100 keV/microm and an indication of a saturation with higher LET. An empirical expression is given approximating the data which may be useful for practical purposes. On the basis of this expression, it is sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…Several researchers reported that the maximum RBE values in LET-RBE curves for mutation induction with around 100 -200 keV/µm were higher than these of other biological endpoints such as cell killing, but the RBE values in the high LET regions over 200 keV/µm were lower than cell killing in previous repots (Tsuboi et al, 1992;Chen et al, 1994;Stoll et al, 1995;Suzuki et al, 1996;Schmidt et al, 1998;Kiefer et al, 2001). The present data of this study showed the same tendency when compared to our data for cell killing using the same culture system (Tsuruoka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers reported that the maximum RBE values in LET-RBE curves for mutation induction with around 100 -200 keV/µm were higher than these of other biological endpoints such as cell killing, but the RBE values in the high LET regions over 200 keV/µm were lower than cell killing in previous repots (Tsuboi et al, 1992;Chen et al, 1994;Stoll et al, 1995;Suzuki et al, 1996;Schmidt et al, 1998;Kiefer et al, 2001). The present data of this study showed the same tendency when compared to our data for cell killing using the same culture system (Tsuruoka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have investigated the biological effects of iron ions using chromosomal aberrations as a biomarker for radiobiological effects (Dini et al, 2005;Durante et al, 2005;Lee et al, 2005;Hada et al, 2007;Pignalosa et al, 2008), however only limited reports have been available about mutation induction in normal human cells induced by iron ions. It is well known that high-LET radiation such as heavy ions is more effective than low-LET radiation such as X and gamma rays for various biological effects such as the cell-killing effect, transformation, chromosome aberration and mutation induction (Skarsgard et al, 1967;Yang et al, 1985;Hei et al, 1988;Alpen et al, 1993;Alpen et al, 1994;Suzuki et al, 2000;Kiefer et al, 2001;Tsuruoka et al, 2005;Suzuki et al, 2006). The RBE values of maximum efficiency for mutation induction were higher than other biological endpoints such as cell killing (Tsuboi et al, 1992;Chen et al, 1994;Stoll et al, 1995;Suzuki et al, 1996;Schmidt et al, 1998;Kiefer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported that the LETrelative biological effectiveness (RBE) curves for different biological endpoints, such as cell killing, mutation induction and in vitro cell transformation are different (Skarsgard et al, 1967;Yang et al, 1985;Tsuboi et al, 1992;Chen et al, 1994;Suzuki et al, 2000;Kiefer et al, 2001;Hamada et al, 2006). It is also known that the peak positions of the LET-RBE curves appear at the LET ranging from 100 to 200 keV/µm, and is shifted to higher LET regions with heavier atomic number ion species even if the LET values are similar (Kraft et al, 1987;Belli et al, 1989;Folkard et al, 1996;Suzuki et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the peak positions of the LET-RBE curves appear at the LET ranging from 100 to 200 keV/µm, and is shifted to higher LET regions with heavier atomic number ion species even if the LET values are similar (Kraft et al, 1987;Belli et al, 1989;Folkard et al, 1996;Suzuki et al, 1997). Also the most effective RBE values are different in different biological endpoints, experimental conditions (Tsuboi et al, 1992;Chen et al, 1994;Kiefer et al, 2001), amount of atomic nuclear fragments and so on.…”
Section: Introductionmentioning
confidence: 99%